Beyond Political Trust. The Role of Professional Skills in the Interpresidential-Permanency of Superintendents in Chile (1990-2014) - Maillet, Antoine (Revista del CLAD Reforma y Democracia, 2017)
The relationship between political authorities and public managers is a foundational theme of the study of public administration, with a strong normative stand on the benefits of stability and professionalization. However, there is a lack of empirical studies on the determinants of stability in positions based on political trust. To fill this gap, this article implements the case study of the superintendents in Chile since the return to democracy who manage to keep their position in spite of the change of presidency. The document proposes three hypotheses. The first one relates stability in the position with individual characteristics of superintendents. The other two take a dynamic and relational approach and focus on the ratification process itself. The second hypothesis is that the skills deployed in office persuade the authority to ratify the superintendent. The third one links stability with the role of the regulated themselves, which may favor permanence. Hypotheses are evaluated based on comparative and process-tracing analysis. The mixed-method analysis of the empirical evidence allows validating the second and third hypothesis, and by doing so highlight the sufficient conditions for stability in the position. The second hypothesis is further deepened with the exposition of the causal mechanism “legitimation by the skills”. This empirical demonstration of the incidence of skills for thestability in public management positions open a research agenda for further studies in the field, both in Chile and Latin America in general.
Keywords: Executive Personnel Administration; Competence; Managerial Capacity; Chile